Thermal analysis of electrodeposited nano-grained Ni-Mo alloys. (September 2018) - Hu, J.; Shi, Y.-N.; Lu, K.
Abstract: Enthalpy release of electrodeposited nano-grained Ni and Ni-Mo alloys with grain size ranging from 29.3 to 5.9 nm and their corresponding annealed samples were investigated by using differential scanning calorimetry. Grain boundary energy of the annealed samples was estimated from enthalpy release and corresponding grain size. Results indicated that the enhanced grain boundary stability in the as-annealed ng Ni-Mo alloys is ascribed to kinetically grain boundary pinning by Mo instead of grain boundary energy reduction. Graphical abstract: Unlabelled Image